2006
DOI: 10.1089/thy.2006.16.85
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Thyroidectomy for Acute Airway Obstruction Caused by a Goiter in a Euthyroid Pregnant Woman

Abstract: Pregnancy constitutes a significant factor for thyroid enlargement. However, acute respiratory failure as a result of airway obstruction from an enlarged thyroid gland is an unusual incident. The case presented here concerns a 27-year-old black woman in her 20th gestational week who underwent an urgent operation for removal of a nontoxic, multinodular, mildly substernal goiter that was causing severe upper airway obstruction leading to acute life-threatening respiratory failure. Diagnosis of an extrathoracic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…About 10% of these patients require emergency airway intubation (4), as in the present case. The causes of acute respiratory failure include upper respiratory tract infections resulting in edema and retention of secretions, sudden intrathyroidal hemorrhage, worsening of a medical illness, and tracheal stenosis or collapse (4,(7)(8)(9). In the present case we believe that the patient suffered from upper airway obstruction because of the giant substernal goiter and also from restrictive lung disease caused by morbid obesity.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…About 10% of these patients require emergency airway intubation (4), as in the present case. The causes of acute respiratory failure include upper respiratory tract infections resulting in edema and retention of secretions, sudden intrathyroidal hemorrhage, worsening of a medical illness, and tracheal stenosis or collapse (4,(7)(8)(9). In the present case we believe that the patient suffered from upper airway obstruction because of the giant substernal goiter and also from restrictive lung disease caused by morbid obesity.…”
Section: Discussionmentioning
confidence: 67%
“…The reported risk of malignancy ranges from 4% to 22% (3), but recent data suggest that the incidence of cancer in substernal goiters is no higher than in cervical goiters (1). Urgent thyroidectomy while rare is necessitated in cases of airway obstruction, both from benign and malignant causes, venous obstruction, and thyrotoxicosis with physiologic compromise (7,9,10). In cases of airway obstruction partial or total thyroidectomy relieved the symptoms (7).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible confounding aetiology is that there are several reported cases of TBM secondary to goitres. These cases are however, generally associated with large compressive goitres and/or tracheal invasion, neither of which were a feature of this case 15–19. Furthermore in a recent review of 1969 patients with large retrosternal goitres, there were few reported cases of postoperative tracheal collapse 20.…”
Section: Discussionmentioning
confidence: 71%
“…[7] There have been 2 case reports involving airway obstruction caused by goiters in pregnant women. [8,9] Three articles were identified reporting rare spontaneous rectus sheath hematoma. [10] We were unable to identify any reports involving spontaneous thyroid hematoma formation in pregnancy or in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%